Composite carbon aerogel material as well as preparation method and application thereof
By preparing composite carbon aerogel materials, using their porous structure and the characteristics of magnesium oxide loading, the problem of insufficient adsorption phosphate speed and capacity of existing phosphorus removal adsorbents is solved, and efficient phosphate removal effect is achieved.
Patent Information
- Application Number
- CN202510205790.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-25
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-02-25
AI Technical Summary
The existing phosphorus removal adsorbents have problems with poor adsorption capacity and slow adsorption rate in adsorbing phosphates, making it difficult to effectively treat phosphorus-containing wastewater and prevent the water from being eutrophied.
A composite carbon aerogel material is used, which consists of a carbon aerogel matrix and magnesium oxide supported on its surface and pore structure. It is prepared by hydrothermal carbonization, vacuum freeze-drying and impregnation and calcining to form a phosphorus removal adsorbent with a porous structure.
This composite carbon aerogel material can significantly improve the adsorption rate and adsorption capacity of phosphate in wastewater, and can reach a phosphorus removal rate of 99.9% within 15 minutes, effectively solving the shortcomings of traditional adsorbents in adsorbing phosphate.
Smart Images

Figure CN119819258A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of adsorption materials, and specifically relates to a composite carbon aerogel material and a preparation method and application thereof. Background Art
[0002] Phosphorus is one of the basic substances involved in the biochemical cycle of the earth. It is a nutrient element necessary for the growth of most plants and plays an extremely important role in industry and agriculture. However, in practical applications, the effective treatment of phosphorus-containing water bodies has become a major problem. Some are even discharged into lakes and rivers without treatment, stimulating the growth of algae, causing eutrophication and algal blooms, which seriously harm the aquatic ecosystem. In order to prevent eutrophication of water bodies, it is necessary to treat phosphates in water bodies. At present, the methods for removing phosphorus from phosphorus-containing wastewater generally include chemical precipitation, biological methods, membrane separation and adsorption. Compared with other phosphorus removal technologies, adsorption has the advantages of simplicity, non-toxicity, low adsorbent cost and high efficiency. It is widely used in the recovery of low-concentration phosphorus solutions and large-scale sewage treatment. Traditional phosphorus removal adsorbents mainly include metal oxides / hydroxides, activated carbon, natural minerals, etc. These traditional adsorbents have the problems of poor adsorption capacity and slow adsorption rate. Summary of the invention
[0003] In view of this, the present invention provides a composite carbon aerogel material and a preparation method and application thereof. The composite carbon aerogel material provided by the present invention has a high adsorption rate and adsorption capacity for phosphate in wastewater, and can efficiently remove phosphate in wastewater.
[0004] In order to solve the above technical problems, the present invention provides a composite carbon aerogel material, comprising a carbon aerogel matrix and magnesium oxide loaded on the surface and pore structure of the carbon aerogel matrix;
[0005] The pore size of the composite carbon aerogel material is 13.7-19.2 nm, and the specific surface area of the composite carbon aerogel material is 47.8-71.6 m 2 / g, the pore volume of the composite carbon aerogel material is 0.307-0.396cm 3 / g.
[0006] Preferably, the mass percentage of magnesium oxide in the composite carbon aerogel material is 10 to 90%.
[0007] The present invention also provides a method for preparing the composite carbon aerogel material described in the above technical solution, comprising the following steps:
[0008] The biomass raw material is hydrothermally carbonized to obtain a biochar hydrogel;
[0009] The biochar hydrogel is subjected to vacuum freeze drying to obtain a carbon aerogel;
[0010] The carbon aerogel is immersed in an impregnation liquid and then calcined to obtain the composite carbon aerogel material; the impregnation liquid is a mixed solution of soluble magnesium salt, urea and ethanol.
[0011] Preferably, the soluble magnesium salt comprises magnesium nitrate or magnesium acetate;
[0012] The molar concentration of the soluble magnesium salt in the impregnation solution is 1 to 1.8 mol / L;
[0013] The molar concentration of urea in the impregnation solution is 0.05-0.25 mol / L.
[0014] Preferably, the mass of the carbon aerogel and the volume ratio of the impregnation liquid are 1 g:8-12 mL.
[0015] Preferably, the immersion temperature is 15 to 30° C. and the immersion time is 12 to 16 hours.
[0016] Preferably, the biomass raw material includes peel;
[0017] The temperature of the hydrothermal carbonization is 170-190° C., and the time is 10-14 hours.
[0018] Preferably, the vacuum degree of the vacuum freeze-drying is 5 to 15 Pa; the temperature of the vacuum freeze-drying is -60 to -40°C; and the time of the vacuum freeze-drying is 24 to 72 hours.
[0019] Preferably, the calcination temperature is 300-600° C., and the heating rate to the required calcination temperature is 1-6° C. / min; the calcination holding time is 1.5-2.5 h.
[0020] The present invention also provides the use of the composite carbon aerogel material described in the above technical solution or the composite carbon aerogel material prepared by the preparation method described in the above technical solution as a dephosphorus adsorbent.
[0021] The present invention provides a composite carbon aerogel material, comprising a carbon aerogel matrix and magnesium oxide loaded on the surface and in the pore structure of the carbon aerogel matrix; the composite carbon aerogel material has a pore structure, the pore diameter of the composite carbon aerogel material is 13.7 to 19.2 nm, and the specific surface area of the composite carbon aerogel material is 47.8 to 71.6 m 2 / g, the pore volume of the composite carbon aerogel material is 0.307-0.396cm 3 / g. In the present invention, the composite carbon aerogel material has a rich pore structure, which enhances the diffusion capacity between phosphate ions and the material, thereby increasing the adsorption rate of phosphate; magnesium oxide is evenly dispersed on the surface and pore structure of the carbon aerogel, and can efficiently adsorb phosphate in the wastewater. The magnesium oxide in the carbon aerogel combines with the entering phosphate ions to form a precipitate. It can be seen from the results of the embodiments that the composite carbon aerogel material provided by the present invention has an adsorption capacity of 364.2 to 392.5 mg / g for phosphorus in wastewater, and can achieve a removal rate of 99.9% within 15 minutes. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 XRD diagram of the composite carbon aerogel material prepared in Examples 1 and 2;
[0023] Figure 2 This is a scanning electron microscope image of the composite carbon aerogel material prepared in Example 1;
[0024] Figure 3 This is a transmission electron micrograph of the composite carbon aerogel material prepared in Example 1;
[0025] Figure 4 It is a columnar comparison chart of the phosphate adsorption capacity of the adsorption materials prepared in Examples 1 to 2 and Comparative Examples 1 to 3;
[0026] Figure 5 It is a dotted line graph of the adsorption capacity of the adsorption materials prepared in Example 1 and Comparative Example 3 at different adsorption times;
[0027] Figure 6 It is a dotted line graph of the phosphorus removal rate of the composite carbon aerogel material prepared in Example 1 at different adsorption times. DETAILED DESCRIPTION
[0028] The present invention provides a composite carbon aerogel material, comprising a carbon aerogel matrix and magnesium oxide loaded on the surface and in the pore structure of the carbon aerogel matrix;
[0029] The pore size of the composite carbon aerogel material is 13.7 to 19.2 nm, and may be 18.5 to 19.2 nm; the specific surface area of the composite carbon aerogel material is 47.8 to 71.6 m 2 / g, can be 47.8~62.5m 2 / g; the pore volume of the composite carbon aerogel material is 0.307-0.396cm 3 / g. In the present invention, the composite carbon aerogel material has a three-dimensional porous network structure.
[0030] As a specific embodiment of the present invention, the mass percentage of magnesium oxide in the composite carbon aerogel material can be 10-90%, can also be 20-80%, and can further be 40-60%.
[0031] The present invention also provides a method for preparing the composite carbon aerogel material described in the above technical solution, comprising the following steps:
[0032] The biomass raw material is hydrothermally carbonized to obtain a biochar hydrogel;
[0033] The biochar hydrogel is subjected to vacuum freeze drying to obtain a carbon aerogel;
[0034] The carbon aerogel is immersed in an impregnation liquid and then calcined to obtain the composite carbon aerogel material; the impregnation liquid is a mixed solution of soluble magnesium salt, urea and ethanol.
[0035] The present invention hydrothermally carbonizes the biomass raw material to obtain a hydrogel of biochar. As a specific embodiment of the present invention, the biomass raw material may include a peel, and the peel may be a watermelon peel, a grapefruit peel, or a cantaloupe peel. As a specific embodiment of the present invention, the hydrothermal carbonization preferably further includes: washing the biomass raw material. The present invention removes impurities such as sludge attached to the surface of the biomass raw material through washing.
[0036] As a specific embodiment of the present invention, the temperature of the hydrothermal carbonization can be 170-190°C, or 175-180°C; the time of the hydrothermal carbonization can be 10-14h, or 12-13h. As a specific embodiment of the present invention, the hydrothermal carbonization can be carried out in a polytetrafluoroethylene reactor.
[0037] As a specific embodiment of the present invention, after the hydrothermal carbonization, the process may further include: immersing the system after the hydrothermal carbonization in an ethanol aqueous solution for impurity removal. As a specific embodiment of the present invention, the volume concentration of the ethanol aqueous solution may be 40-80%, or 50-60%. The present invention can remove organic impurities such as sugars generated during the hydrothermal carbonization process through immersion. The present invention has no special requirements for the amount of the ethanol aqueous solution, the immersion time, and the number of immersions, as long as the impurities in the system after the hydrothermal carbonization can be removed. As a specific embodiment of the present invention, after the immersion, the process may further include: performing solid-liquid separation on the immersed system to obtain a biochar hydrogel. As a specific embodiment of the present invention, the solid-liquid separation may be filtration, and the present invention has no special requirements for the filtration, and the conventional method in the art may be used.
[0038] After obtaining the biochar hydrogel, the present invention vacuum freeze-dries the biochar hydrogel to obtain carbon aerogel. As a specific embodiment of the present invention, the vacuum degree of the vacuum freeze-drying can be 5 to 15 Pa, or 5 to 10 Pa; the temperature of the vacuum freeze-drying can be -60 to -40°C, or -45 to -55°C; the time of the vacuum freeze-drying can be 24 to 72 hours, or 36 to 48 hours. The present invention adopts a vacuum freeze-drying method to avoid the collapse of the carbon aerogel structure. In the present invention, the carbon aerogel is brown.
[0039] After obtaining the carbon aerogel, the present invention places the carbon aerogel in an impregnation solution and then calcines it to obtain the composite carbon aerogel material. In the present invention, the impregnation solution is a mixed solution of soluble magnesium salt, urea and ethanol. As a specific embodiment of the present invention, the soluble magnesium salt may include magnesium nitrate or magnesium acetate, and the magnesium nitrate may be magnesium nitrate hexahydrate; the molar concentration of the soluble magnesium salt in the impregnation solution may be 1-1.8 mol / L, or 1.2-1.6 mol / L, or further 1.4-1.5 mol / L; the molar concentration of urea in the impregnation solution may be 0.05-0.25 mol / L, or 0.1-0.2 mol / L; the mass of the carbon aerogel and the volume ratio of the impregnation solution may be 1g:8-12mL, or 1g:9-10mL. In the present invention, ethanol, as a solvent for urea and soluble magnesium salt, can be absorbed by the carbon aerogel faster. The present invention adds urea to the impregnation solution to form a pore structure during the calcination process, which is beneficial for phosphate ions to quickly enter the composite carbon aerogel material and accelerate the adsorption rate. The soluble magnesium salt can be converted from magnesium ions to magnesium oxide during the calcination process to form a porous structure on the carbon aerogel. The present invention can adjust the size of the pore structure in the composite carbon aerogel material by adjusting the amount of urea used.
[0040] As a specific embodiment of the present invention, the immersion temperature can be 15 to 30° C., or 20 to 25° C.; the immersion time can be 12 to 16 hours, or 13 to 15 hours.
[0041] As a specific embodiment of the present invention, the impregnation may further include: volatilizing the solvent in the impregnation system, and calcining the solid obtained after the solvent volatilization. The present invention has no special requirements for the solvent volatilization, and a conventional volatilization method in the art can be used, such as natural volatilization.
[0042] As a specific embodiment of the present invention, the calcination temperature can be 300-600°C, specifically 300°C, 350°C, 400°C, 450°C, 500°C, 550°C or 600°C; the heating rate to the required temperature for calcination can be 1-6°C / min, specifically 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min or 6°C / min; the calcination holding time can be 1.5-2.5h, specifically 1.5h, 1.8h, 2h, 2.3h or 2.5h. As a specific embodiment of the present invention, the calcination can be carried out under a protective atmosphere, which can be a nitrogen atmosphere or an argon atmosphere.
[0043] The present invention uses waste biomass as raw materials to prepare carbon aerogels, and forms a dephosphorization adsorption material with a porous structure by co-pyrolysis of magnesium salt, urea and carbon aerogel. The material source used in the preparation method provided by the present invention is abundant, cheap and easy to obtain, and the synthesis method is simple and green; the prepared composite carbon aerogel material has an extremely fast dephosphorization rate. The composite carbon aerogel material prepared by the present invention has a good application prospect in water purification.
[0044] The present invention also provides the use of the composite carbon aerogel material described in the above technical solution or the composite carbon aerogel material prepared by the preparation method described in the above technical solution as a dephosphorization adsorbent. As a specific embodiment of the present invention, the method for dephosphorizing wastewater using the composite carbon aerogel material as a dephosphorization adsorbent may include the following steps:
[0045] The composite carbon aerogel material is placed in phosphorus-containing wastewater for adsorption and phosphorus removal.
[0046] As a specific embodiment of the present invention, the phosphorus concentration in the phosphorus-containing wastewater can be 1-50 mg / L, or 5-30 mg / L; the ratio of the mass of the composite carbon aerogel material to the volume of the phosphorus-containing wastewater can be 100-500 mg:1L, or 200-400 mg:1L; the time for adsorption and phosphorus removal can be 3-24 hours, or 10-12 hours.
[0047] In order to further illustrate the present invention, the technical solutions provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0048] Example 1
[0049] The surface of the discarded watermelon peel was cleaned and then placed in a polytetrafluoroethylene reactor, and then hydrothermally carbonized at 180°C for 12 hours, and then immersed in a 50% ethanol aqueous solution to remove impurities, and then filtered to obtain a biochar hydrogel;
[0050] The biochar hydrogel was freeze-dried at a vacuum degree of 10 Pa and a temperature of -50°C for 48 hours to obtain a carbon aerogel material;
[0051] 1 g of carbon aerogel material was immersed in 10 mL of a mixed solution of magnesium nitrate hexahydrate, urea and ethanol (the molar concentration of magnesium nitrate was 1.4 mol / L, and the molar concentration of urea was 0.1 mol / L) at 25°C for 12 h, and the solution was allowed to evaporate naturally; the solid obtained after the volatilization of the solution was heated to 450°C in a tubular furnace in a nitrogen atmosphere at a heating rate of 2°C / min and calcined for 2 h to obtain a composite carbon aerogel material.
[0052] Example 2
[0053] The composite carbon aerogel material was prepared according to the method of Example 1, except that the molar concentration of urea in the mixed solution of magnesium nitrate hexahydrate, urea and ethanol was adjusted from 0.1 mol / L to 0.2 mol / L.
[0054] Comparative Example 1
[0055] 1.4 mol of magnesium nitrate hexahydrate and 0.1 mol of urea were mixed, and the mixture was heated to 450° C. at a heating rate of 2° C. / min in a tubular furnace under a nitrogen atmosphere and calcined for 2 h to obtain an adsorption material free of carbon aerogel.
[0056] Comparative Example 2
[0057] The adsorption material was prepared according to the method of Example 1, except that the mixed solution of magnesium nitrate hexahydrate, urea and ethanol was replaced with an ethanol solution of urea with a molar concentration of 0.1 mol / L to obtain an adsorption material without magnesium element.
[0058] Comparative Example 3
[0059] An adsorbent material was prepared according to the method of Example 1, except that the mixed solution of magnesium nitrate hexahydrate, urea and ethanol was replaced with an ethanol solution of magnesium nitrate with a molar concentration of 1.4 mol / L to obtain an adsorbent material without urea.
[0060] The composite carbon aerogel material prepared in Examples 1 and 2 was subjected to X-ray diffraction detection to obtain an XRD spectrum, as shown in FIG. Figure 1 As shown. Figure 1 It can be seen that the composite carbon aerogel material provided by the present invention contains MgO.
[0061] The composite carbon aerogel material prepared in Example 1 was subjected to scanning electron microscopy to obtain a SEM image, as shown in FIG. Figure 2 The adsorbent material prepared in Example 1 was tested by transmission electron microscopy to obtain a TEM image, as shown in FIG. Figure 3 As shown. Figure 2 , 3 It can be seen that the composite carbon aerogel material provided by the present invention has a three-dimensional porous network structure.
[0062] The adsorption materials prepared in Examples 1 to 2 and Comparative Examples 1 to 3 were subjected to nitrogen physical adsorption and desorption testing to obtain pore data, which are listed in Table 1.
[0063] Table 1 Pore data of different adsorption materials
[0064] Example <![CDATA[BET specific surface area (m 2 / g)]]> Pore size (nm) <![CDATA[Pore volume (cm 3 / g)]]> Comparative Example 1 5.9 24.1 0.034 Comparative Example 2 86.4 21.0 0.071 Comparative Example 3 71.6 13.7 0.351 Example 1 62.5 18.5 0.396 Example 2 47.8 19.2 0.307
[0065] 5 mg of the adsorbent material prepared in Examples 1 to 2 and Comparative Examples 1 to 3 were placed in a 100 mL beaker, and 50 mL of a phosphorus-containing aqueous solution (KH2PO4 solution) with a phosphorus concentration of 50 mg / L (based on the P content in KH2PO4) was added, respectively. After mixing, the adsorption was carried out for 12 hours. The P concentration in the solution was measured by sampling, and the adsorption capacity of the above adsorbent material for phosphorus (based on phosphorus) was calculated. The results are as follows: Figure 4 As shown. Figure 4 It can be seen that the adsorption material provided by the present invention has excellent adsorption performance for phosphorus.
[0066] The adsorption materials prepared in Example 1 and Comparative Example 3 were respectively immersed in a KH2PO4 standard solution with a P concentration of 50 mg / L at room temperature (25°C) for adsorption, and samples were taken for detection at the following adsorption times: 5min, 10min, 15min, 25min, 40min, 55min, 85min, 115min, 145min and 205min; the detection method was to determine the phosphorus concentration by molybdenum blue spectrophotometry (Chinese Standard GB 11893-89), and the test results (in terms of P) are listed in Table 2.
[0067] Table 2 Adsorption capacity of adsorbent materials at different adsorption times
[0068]
[0069] According to Table 2, a dotted line graph of the adsorption capacity of the adsorbent materials prepared in Example 1 and Comparative Example 3 at different adsorption times is drawn, as shown in FIG. Figure 5 Combining Table 2 and Figure 5 It can be seen that the adsorption material provided by the present invention has a fast phosphorus removal rate.
[0070] 25 mg of the composite carbon aerogel material prepared in Example 1 was immersed in a natural actual water body with a P concentration of 3.3 mg / L at room temperature (25°C) for adsorption. Samples were taken at the following adsorption times: 1 min, 3 min, 5 min, 7 min, 10 min, and 15 min. The molybdenum blue spectrophotometry (Chinese Standard GB 11893-89) was used to determine the phosphorus concentration. The test results (in terms of P) are listed in Table 3.
[0071] Table 3 Removal rate of phosphorus in natural water by composite carbon aerogel material prepared in Example 1
[0072] Adsorption time (min) 1 3 5 7 10 15 Removal rate (%) 83.1 94.8 96.5 97.3 98.3 99.9
[0073] According to Table 3, a dotted line graph of the phosphorus removal rate of the composite carbon aerogel material prepared in Example 1 at different adsorption times is drawn, as shown in FIG. Figure 6 shown.
[0074] Combining Table 3 and Figure 6 It can be seen that the composite carbon aerogel material provided by the present invention has a fast phosphorus removal rate and can achieve a removal rate of 99.9% within 15 minutes.
[0075] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A composite carbon aerogel material, characterized in that: It comprises a carbon aerogel matrix and magnesium oxide loaded on the surface and pore structure of the carbon aerogel matrix; The pore size of the composite carbon aerogel material is 13.7-19.2 nm, and the specific surface area of the composite carbon aerogel material is 47.8-71.6 m 2 / g, the pore volume of the composite carbon aerogel material is 0.307-0.396cm 3 / g.
2. The composite carbon aerogel material according to claim 1, characterized in that: The mass percentage of magnesium oxide in the composite carbon aerogel material is 10-90%.
3. The method for preparing the composite carbon aerogel material according to claim 1 or 2, characterized in that: The following steps are involved: The biomass raw material is hydrothermally carbonized to obtain a biochar hydrogel; The biochar hydrogel is subjected to vacuum freeze drying to obtain a carbon aerogel; The carbon aerogel is placed in an impregnation liquid, impregnated, and then calcined to obtain the composite carbon aerogel material; The impregnation solution is a mixed solution of soluble magnesium salt, urea and ethanol.
4. The preparation method according to claim 3, characterized in that: The soluble magnesium salt includes magnesium nitrate or magnesium acetate; The molar concentration of the soluble magnesium salt in the impregnation solution is 1 to 1.8 mol / L; The molar concentration of urea in the impregnation solution is 0.05-0.25 mol / L.
5. The preparation method according to claim 3 or 4, characterized in that: The mass of the carbon aerogel and the volume ratio of the impregnation liquid are 1 g:8-12 mL.
6. The preparation method according to claim 3, characterized in that: The immersion temperature is 15 to 30° C. and the immersion time is 12 to 16 hours.
7. The preparation method according to claim 3, characterized in that: The biomass raw material includes peel; The temperature of the hydrothermal carbonization is 170-190° C., and the time is 10-14 hours.
8. The preparation method according to claim 3, characterized in that: The vacuum degree of the vacuum freeze drying is 5 to 15 Pa; the temperature of the vacuum freeze drying is -60 to -40°C; and the time of the vacuum freeze drying is 24 to 72 hours.
9. The preparation method according to claim 3, characterized in that: The calcination temperature is 300-600°C, and the heating rate to the required calcination temperature is 1-6°C / min; the calcination insulation time is 1.5-2.5h.
10. Use of the composite carbon aerogel material according to claim 1 or 2 or the composite carbon aerogel material prepared by the preparation method according to any one of claims 3 to 9 as a dephosphorus adsorbent.
Citation Information
Patent Citations
Preparation method and application of cellulose / graphene oxide carbon aerogel
CN109019597A
Preparation method and application of biochar-loaded iron-manganese material
CN111617742A
Adsorbing material as well as preparation method and application thereof
CN118767872A
Preparation method of carbon aerogel for air purification
CN119425629A
Cited By
Bi-crosslinked carbon aerogel as well as preparation method and application thereof
CN121266558A